2015
DOI: 10.1007/s00223-015-9994-4
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Filamin A in Monocytes Protects Cortical and Trabecular Bone from Post-menopausal Changes in Bone Microarchitecture

Abstract: The objective of the study was to determine the in vivo role of Filamin A (FLNA) in osteoclast generation and function, through the assessment of trabecular bone morphology, bone turnover, and the resulting changes in mechanical properties of the skeleton in mice with targeted deletion of FLNA in pre-osteoclasts. Using a conditional targeted knockdown of FLNA in osteoclasts, we assessed bone characteristics in vivo including micro-computed tomography (micro-ct), histomorphometric analyses, and bone mechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The FLNA gene encodes for actin-binding protein or filamin that crosslinks actin filaments into orthogonal networks in the cortical cytoplasm and plays a role in anchoring membrane proteins to the actin cytoskeleton (Stossel et al 2001; Razinia et al 2012). FLNA is required for monocyte migration during osteoclastogenesis via its role in regulating Rho GTPase-mediated actin remodeling (Leung et al 2010; Goldberg et al 2015). FLNA also interacts with low-density lipoprotein receptor-related protein 6 (LRP6) to inhibit β-catenin expression and enhances NFATc1-dependent osteoclastogenic gene expression to inhibit osteogenesis and promote osteoclastogenesis (Yang et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The FLNA gene encodes for actin-binding protein or filamin that crosslinks actin filaments into orthogonal networks in the cortical cytoplasm and plays a role in anchoring membrane proteins to the actin cytoskeleton (Stossel et al 2001; Razinia et al 2012). FLNA is required for monocyte migration during osteoclastogenesis via its role in regulating Rho GTPase-mediated actin remodeling (Leung et al 2010; Goldberg et al 2015). FLNA also interacts with low-density lipoprotein receptor-related protein 6 (LRP6) to inhibit β-catenin expression and enhances NFATc1-dependent osteoclastogenic gene expression to inhibit osteogenesis and promote osteoclastogenesis (Yang et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The FLNA gene encodes for actin-binding protein or filamin that crosslinks actin filaments into orthogonal networks in the cortical cytoplasm and plays a role in anchoring membrane proteins to the actin cytoskeleton (56,57) . FLNA is required for monocyte migration during osteoclastogenesis via its role in regulating Rho GTPase-mediated actin remodeling (58,59) .…”
Section: Discussionmentioning
confidence: 99%
“…( 53 ) showed that FLNA accumulates in the osteoblasts, and the osteoclasts were observed in the human OP samples. A report suggests that negative regulation of FLNA in mice is age-related and postmenopausal osteoporosis in vitro osteogenic differentiation in OP promotes RANKL-induced osteoclast differentiation ( 54 ). Zhang X et al.…”
Section: Discussionmentioning
confidence: 99%